2017
DOI: 10.1002/2016ja023018
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric response and reconfiguration times following IMF By reversals

Abstract: The interaction between the interplanetary magnetic field (IMF) and the geomagnetic field at the dayside magnetopause leads to transfer of momentum and energy which changes the magnetospheric configuration, but only after a certain time. In this study we quantify this time, to advance our understanding of the causes for the delayed response of the magnetosphere. We study the response and reconfiguration time of the inner magnetosphere to IMF By reversals. A superposed epoch analysis of magnetic field measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 55 publications
(108 reference statements)
13
49
2
Order By: Relevance
“…The second very important factor is the contribution from the dayside Region 1 currents, whose intensification under southward IMF conditions, combined with their IMF B -induced overlapping in the noon sector results in large azimuthal fields, strongly correlated with the IMF B (e.g., , and references therein). As far as we know, the IMF B effects in the near-equatorial dayside region were studied only on the basis of geostationary measurements (Tenfjord et al, 2017(Tenfjord et al, , 2018Wing et al, 1995) and our obtained penetration coefficients 0.2-0.4 agree with those previous results. In this test example we set IMF B = +5 nT; it should also be noted in passing that, due to the assumed linear dependence of the model field on the IMF B (equations (6)- (7)), reversing the IMF B orientation does not affect the shape of the internal equatorial B distribution nor its absolute magnitude but only reverses its polarity.…”
Section: Global Modeling Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The second very important factor is the contribution from the dayside Region 1 currents, whose intensification under southward IMF conditions, combined with their IMF B -induced overlapping in the noon sector results in large azimuthal fields, strongly correlated with the IMF B (e.g., , and references therein). As far as we know, the IMF B effects in the near-equatorial dayside region were studied only on the basis of geostationary measurements (Tenfjord et al, 2017(Tenfjord et al, , 2018Wing et al, 1995) and our obtained penetration coefficients 0.2-0.4 agree with those previous results. In this test example we set IMF B = +5 nT; it should also be noted in passing that, due to the assumed linear dependence of the model field on the IMF B (equations (6)- (7)), reversing the IMF B orientation does not affect the shape of the internal equatorial B distribution nor its absolute magnitude but only reverses its polarity.…”
Section: Global Modeling Resultssupporting
confidence: 87%
“…Several interesting features can be seen in the plots. Note in this regard that a qualitatively similar result was found by Tenfjord et al (2017Tenfjord et al ( , 2018 and Cao et al (2014). The effect is clearly seen even in the noon area, where the penetration coefficient can reach nearly 0.4 (right panel).…”
Section: Global Modeling Resultssupporting
confidence: 82%
“…Motoba et al (2011) and Rong et al (2015) suggested with the several case studies that penetration timescale can be 1-2 hr. Tenfjord et al (2017) concluded that the delay of magnetospheric reconfiguration to B i y polarity change at geostationary orbit is from 15 to 45 min. This publication also contains a detailed review of other relevant issues.…”
Section: Introductionmentioning
confidence: 99%
“…On the nightside IMF delay depends on the solar wind velocity. For maintaining the IMF delay for the nighside auroral zone, we have delayed the IMF data by 60 min (Tenfjord et al, 2017). This delay in the IMF data is with respect to the ACE measurements, which maintains the propagation delay of the solar wind from the bow to the magnetotail lobe (Kullen et al, 2015).…”
Section: Superdarn Radar Datamentioning
confidence: 99%
“…Figure 2E, shows the IMF condition during the BBAE event of 27 January 2015 between 20:30 and 23:00 UT. Please keep in mind that we have delayed the IMF data by 60 min (Tenfjord et al, 2017). IMF B x (in blue line) has a negative value (∼−5 nT) from 20:30 to 22:40 UT.…”
Section: Bouncing Boundary Auroral Emissions (Bbae)mentioning
confidence: 99%